THE EFFECTS OF RACIAL DISCRIMINATION FOR FAMILIES IN THE FREEDOM WRITERS MOVIE DIRECTED BY RICHARD LAGRAVENESE (2007): A SOCIOLOGICAL APPROACH - PAMUNGKAS, DESI TRI LESTYO (2011)
The objectives of the study are (1) to analyze Freedom Writers movie based on its structural elements, (2) to analyze the effect of racial discrimination for families in the Freedom Writers movie based on the sociological approach. In collecting the data the writer uses library research. The data are collected from the books, articles and other resources related to the topic. This research employs the theory of sociological of literature, major principal of sociological of literature, and structure elements of the movie. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound and editing are related to each other and form the unity into good quality of a movie. Second, based on the sociological analysis, there is close relation between the movie production and the social reality underlying it, such as the global issues of human right and heroism. This movie also criticizes the tendency of imposing the cultural values of the dominant group over the minority.